Effects of multicomponent exercise training on muscle oxygenation in young and older adults - Tai-You Lin; Jia-Jin J. Chen; Linda L. Lin; Wei-Tsun Ou Yang; Meng-Yu Chen; Yueh-Chang Tsai (Journal of Exercise Science & Fitness, 2023)
Background/Objective: Though multicomponent exercise training was found beneficial in improving the physical functionality, the effects of multicomponent exercise training on muscle oxygenation are still unclear. The purpose of this study was to investigate the effects of multicomponent exercise training on muscle oxygenation in young and older participants. Methods: In this study, 17 young adults (Y) and 18 healthy older adults (E) were recruited to receive a multicomponent exercise training for 12 weeks, 2–3 sessions per week. Muscle oxygenation, muscle strength, and electromyography data were collected and compared pre- and post-training. Muscle oxygen saturation (SpO2) during isometric knee extension tests involving voluntary contraction (VOL) and electrical stimulation (ES) was measured by near-infrared spectroscopy. The SpO2 kinetics in the contraction and recovery phases were calculated using a tangential model to extract ΔSpO2 and inflection time (IF). Results: Muscle strength significantly increased in the post-training (234.31 ± 83.2 N·m, p < 0.05). The post-training ΔSpO2 of the ES in the Y (8.43 ± 5.35%) significantly increased and was higher than that in the E (2.78 ± 3.03%, p < 0.05). In the recovery phase, the post-training IF of VOL (7.07 ± 3.31s) was significantly shorter than that of the pre-training period (8.73 ± 4.46s, p < 0.05). Additionally, the median frequency of electromyography significantly decreased in the post-training period (103.84 ± 21.75 Hz, p < 0.05). Conclusion: The multicomponent exercise training improved the muscle strength, neuromuscular performance, and muscle aerobic function irrespective of age. The primary adaptation of the muscles to the multicomponent exercise training between the two groups varied.